FENOMENA LATTE FACTOR PADA GENERASI Z JABODETABEK: PENGARUH CASHLESS SOCIETY, PROMOSI DIGITAL, DAN LITERASI KEUANGAN - Maharani, Calista Vania; Bidhari, Sandhika Cipta (Politeknik Negeri Ambon, 2025)
Introduction: This study aims to analyse the influence of the cashless society, digital promotion, and financial literacy on the increase of the latte factor among Generation Z in the Jabodetabek area. The Latte Factor refers to small, recurring expenses that may seem insignificant, such as coffee, snacks, or digital subscriptions, but can accumulate over time and significantly impact personal finances. The rise of cashless payment systems and widespread digital marketing strategies, including cashback, free shipping, and flash sales, has amplified this behaviour. Meanwhile, financial literacy is expected to moderate such impulsive spending tendencies.Methods: This study employs a quantitative methodology based on a survey to investigate how the three independent factors influence the rise of the latent factor. Using purposive sampling, 115 respondents from Jabodetabek's Generation Z were chosen for the study. Multiple linear regressions were used to analyse and evaluate the data using SPSS version 26.Results: According to the statistics, a cashless culture and digital advertising positively impact the expansion of the latte factor. On the other hand, financial literacy negatively affects it. These findings suggest that convenience in transactions and exposure to online promotions encourage unplanned small expenditures, whereas higher financial literacy helps reduce such behaviour. Keywords: Cashless Society, Digital Promotion, Financial Literacy, Generation Z, Latte Factor